An Approach for Peg-in-Hole Assembling using Intuitive Search Algorithm based on Human Behavior and Carried by Sensors Guided Industrial Robot. Issue 3 (2015) - Abdullah, Mustafa W.; Roth, Hubert; Weyrich, Michael; Wahrburg, Jürgen
Abstract: Automated peg-in-hole assembling approach using Force/Torque sensor and vision system is presented in this research. The complicity of the assembling task due to parts' geometries or position uncertainty in work area are the main factors for the lack of fully automated assembling approaches nowadays in industry and specially in the automotive sector. Based on human operator handling for the assembling of peg-in-hole, an algorithm consists of six phases is developed. In one of the phases a model is created to determine the location of the hole's center during the insertion by using Force/Torque sensor data. The contact forces and torques in each step of the proposed assembling algorithms that was carried by a six degree-of-freedom (DOF) industrial robot is presented.